FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN PERILAKU TIDAK ETIS SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Perusahaan BUMN di Kota Pekanbaru) - Jessy Rhutsye permata Sari Sumolang; Yusralaini Yusralaini; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to examine the effect of effectiveness of internal control, suitability of compensation, compliance of accounting rules, information asymmetry and management morality towards the tendency of accounting fraud. Then, to examine the effect of unethical behavior on the tendency of accounting fraud. Then, the last to examine the effect of effectiveness of internal control, suitability of compensation, compliance of accounting rules, asymmetry of information and management morality towards the tendency of accounting after mediation by unethical behavior. The population of this research is the head of accounting department and financial staff who work in a State-Owned Company in Pekanbaru City. The sample of this research are 147 respondents selected based on criteria in purposive sampling. Data were analyzed using Partial Least Square (PLS) in a of Structural Equation Modeling (SEM). The result showed that the effectiveness of internal control, suitability of compensation, information asymmetry have effect towards the tendency of accounting fraud. Meanwhile the compliance of accounting rules and management morality have no effect on tendency of accounting fraud. Then the effectiveness of internal control, compliance of accounting rules, and management morality have effect towards unethical behavior. On the other hand, the suitability of compensation and information asymmetry have no effect on unethical behavior. The result of this research also showed that that the unethical behavior has effect on tendency of accounting fraud. Then the effectiveness of internal control, compliance of accounting rules, and management morality have effect towards the tendency of accounting fraud through unethical behavior as an intervening variable. However, the suitability of compensation and information asymmetry have no effect on tendency of accounting fraud through unethical behavior as an intervening variable.Keywords : Tendency of Accounting Fraud, Unethical Behavior, Effectiveness of Internal Control, Suitability of Compensation, Compliance of Accounting Rules, Information Asymmetry, and Management Morality